Delayed cerebral ischaemic injury following apparent recovery from Streptococcus pneumoniae meningitis. Issue 5 (2nd September 2016) - Wittebole, Xavier; Duprez, Thierry; Hantson, Philippe
Abstract : Two patients were admitted to the Emergency Department with fever and altered consciousness. The diagnosis of Streptococcus pneumoniae meningitis was rapidly obtained from cerebrospinal fluid (CSF) culture. Their neurological condition rapidly improved after the introduction of antimicrobial therapy plus dexamethasone. The brain's computed tomography on admission did not reveal any specific lesion. By the second week of treatment, while CSF was sterile, their neurological condition gradually worsened and both died from extensive brain ischaemic lesions. While persisting inflammation could be the underlying mechanism, these observations illustrate that such complications are not fully prevented by a short course of high dose steroids.